CuInS2 Quantum Dot and Polydimethylsiloxane Nanocomposites for All‐Optical Ultrasound and Photoacoustic Imaging (Adv. Mater. Interfaces 20/2021). Issue 20 (22nd October 2021) - Bodian, Semyon; Colchester, Richard J.; Macdonald, Thomas J.; Ambroz, Filip; Briceno de Gutierrez, Martha; Mathews, Sunish J.; Fong, Yu Man Mandy; Maneas, Efthymios; Welsby, Kathryn A.; Gordon, Ross J.; Collier, Paul; Zhang, Edward Z.; et al.
Abstract : Nanocomposites for Multimodality Optical Ultrasound and Photoacoustic Imaging In article number 2100518, Semyon Bodian, Richard J. Colchester, and co‐workers develop a nanocomposite by integrating CuInS2 quantum dots within a polydimethylsiloxane matrix and deposited onto the distal end of an optical fiber. The wavelength‐selective optical absorption enables co‐registered all‐optical ultrasound and photoacoustic imaging, using absorbed laser light for ultrasound generation and transmission of photoacoustic excitation light. This nanocomposite will enable molecular and microstructural clinical imaging particularly intravascular imaging. Figure design: Amy Warnock.